Dynamic tracking of human umbilical cord mesenchymal stem cells (hUC-MSCs) following intravenous administration in mice model - Sze-Piaw Chin; Marini Marzuki; Lihui Tai; Nurul Ashikin Mohamed Shahrehan; Christine Ricky; Audrey Fanty; Annas Salleh; Chui Thean Low; Kong-Yong Then; Susan Ling Ling Hoe; Soon Keng Cheong (Regenerative Therapy, 2024)
Introduction: In the past decades, human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) have sparked interest in cellular therapy due to their immunomodulatory properties. Nevertheless, the fate of hUC-MSCs in the body remains poorly understood. This study aimed to investigate the biodistribution, homing and clearance of systemically administered hUC-MSCs in healthy BALB/c mice model. Methods: hUC-MSCs were labelled with GFP-Luc2 protein, followed by characterisation with flow cytometry. Upon intravenous infusion of transduced hUC-MSCs into the healthy BALB/c mice, the cells were dynamically monitored through the bioluminescent imaging (BLI) approach. Results: Transduction of hUC-MSCs with GFP-Luc2 not only preserved the characteristics of MSCs, but also allowed live monitoring of transduced cells in the mice model. Upon systemic administration, BLI showed that transduced hUC-MSCs first localised predominantly in the lungs of healthy BALB/c mice and mainly remained in the lungs for up to 3 days before eventually cleared from the body. At terminal sacrifice, plasma chemistry biomarkers remained unchanged except for C-peptide levels, which were significantly reduced in the hUC-MSCs group. Histopathological findings further revealed that hUC-MSCs infusion did not cause any adverse effects and toxicity to lung, liver and heart tissues. Conclusions: Collectively, systemically administrated hUC-MSCs was safe and demonstrated dynamic homing capacity before eventually disappearing from the body.